A Novel Structure to Suppress Transverse Modes in Radio Frequency TC-SAW Resonators and Filters - Liu, Yuhao; Liu, Jiansong; Wang, Yiliu; Lam, C. S. (IEEE microwave and wireless components letters, 2019)
In this letter, we present simulation and measurement results of a novel structure to suppress transverse modes in radio frequency temperature-compensated surface acoustic wave (TC-SAW) resonators and filters. We propose a bent TC-SAW resonator structure to suppress such transverse modes which in general trapped between the busbars, based on the fact that higher TC-SAW wave modes in the resonator suffer higher loss at the resonator boundary. The higher wave modes leak energy out from the resonator busbars after multiple bounces along the length of the resonator. By adding this structure to our existing transverse mode suppression technique, we successfully suppress the bulk of the transverse modes in the resonators and filters. To test the effectiveness of the proposed structure, we fabricate the bent resonators and filters in a standard TC-SAW fabrication process on 128YX lithium niobate (128YX-LN) substrate. The measured long-term evolution band 39 filter response shows the effectiveness of this structure in suppressing transverse modes.